Are contributory causes of death in part 2 of the death certificate mediators of chains of morbid events leading to death? - Elizabet Ukolova (Population Health Metrics)
Abstract Background In the United States, over half of all deaths are attributed to five leading underlying causes of death (at the ICD-3 digit level). However, these underlying causes represent only 25% of the total medical information documented on death certificates. While previous studies have investigated associations between causes of death, none have specifically examined the mechanisms of interaction among these causes. This study aims to explore the role of contributory causes of death recorded in Part 2 of the death certificate in the lethal process. Methods Working with U.S. Multiple Cause of Death Microdata in 2019, we use causal pie models to model the synergy between multiple causes of death. Results The findings show how contributory causes in Part 2 affect the sequence of morbid events leading to death. Three broad categories of roles can be distinguished: (i) some contributory causes act as mediators in the chain of morbid events, (ii) others do not exhibit any interaction with the conditions listed in Part 1, and (iii) some might play a role in the development of underlying causes. Conclusion Contributory causes listed in Part 2 play a crucial role in transitions to terminal morbid states. There is evidence that these are more than just conditions without a direct relationship to the underlying cause of death.